From Early Monasticism to Later Ascetism in Central Italy: Ascetic Life and Rock Art in the Grottoes of the Suppentonia Valley in Northern Latium between the 6th and the 11th Century - Scungio, Elisabetta (Actual Problems of Theory and History of Art, 2016)
This article aims to investigate the early monastic occupation of the Suppentonia valley, set in Northern Latium (Central Italy), 50 km far from Rome. Thanks to the sources, it is known that many hermits settled there since the 6th century, at least exploiting the isolation and the natural mysticism of the site. In fact, plenty of minuscule grottoes are still visible excavated in the tuff (the local volcanic rock) in the cliff sides, where anchorites — among them there were Saint Anastasius and Nonnosus, cited by Pope Gregory the Great in his Dialogues — used to spend their secluded life. It is highly probable that they shared common liturgy and prayer, just like in Syro-Palestinian monasteries (lauras), as it seems from the presence of a larger three-room grotto provided with liturgical furnishings and paintings, presumably a rupestrian church. This is commonly known as grotto of Saint Leonard, because of a painted votive panel depicting that holy hermit inside there. The altar in the grotto — opened by a niche for relics in its basement and covered by an arched recess — seems to be dating from the 6th century. This early dating fostered a link between the church and the Langobardic invasion of the near-by area: a local legend reports that in the early 7th century it was the place where Pope Gregory the Great met queen Teodolinda — king Agilulf ’s wife — trying to stop the descent to Rome of that people. Anyway, no historic evidence proves that fact really happened. In spite of this, there certainly was a prolonged use of the site, considering the painted shreds still surviving on the sidewalls. They can be dated to the 11th century and probably they have to be put in connection with the great revival of ascetism all over Europe at that time, perhaps being made by the same hermits who settled there. Moreover, a later continuity of use of the site in the 14th century is certain because of the painting depicting Saint Leonard, which can be dated to that time for its colors and style.